Digital marketing communication strategy in the post-pandemic of the Indonesian tourism - Tri Waluyo (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Digital Marketing Communication Strategy something that every tourism industry should have for tourist activities describes the main users of digital technology supporting the marketing functions of an organization. In an effort to improve marketing and reach the target market through regular and organized digital marketing. Tourism needs a digital marketing communication strategy to help and serve the needs of the community, effective and efficiently planned strategies so that the success rate is high. This study aims to determine the digital marketing communication strategy in the Post-Pandemic of the Indonesian Tourism. The method used by this study is descriptive qualitative. The results of this study are advertising, personal selling, sales promotion, direct marketing, public relations, and Word-of-Mouth (WOM) Marketing.